Long-Term Observation of Mediterranean Ecosystems with Satellite Remote Sensing - Hill, Joachim; Hostert, Patrick; Röder, Achim (Recent Dynamics of the Mediterranean Vegetation and Landscape, 2005)
This chapter contains sections titled: * Introduction * Remote Sensing Concepts * The Analysis of Environmental Change with Landsat Satellites * Discussion * Acknowledgements
Keywords: earth observation satellites; Landsat data; Linear Spectral Mixture Analysis; Mediterranean ecosystems; NOAA-AVHRR1 satellite system; satellite remote sensing; semi-natural ecosystems; SPOT-satellite; vegetation dynamics (citation)